GREGORY LEYH’S APPROACH TO CONSTITUTIONAL HERMENEUTICS: A CRITICAL ANALYSIS OF LEGAL HERMENEUTICS ACCORDING TO HANS-GEORG GADAMER - Hermawan, Muhammad Ilham (Faculty of Law, Universitas Diponegoro, 2025)
Constitutional interpretation is a crucial and evolving field that extends beyond judges, involving legal scholars, citizens, and political theorists. It encompasses various methods such as originalism, textualism, moral reasoning, structural reasoning, and comparative constitutional law, each offering distinct approaches to understanding the Constitution. These methods are often categorized into two schools of thought: originalist and non-originalist. The debate between these two approaches has been a source of recurring controversy, with originalism advocating for adherence to the framers’ intentions and non-originalism promoting a more dynamic, “living” interpretation. Terence Ball emphasizes the significance of constitutional interpretation, dubbing it “deadly hermeneutics,” as a nation’s fate hinges on how its Constitution is understood and applied. While traditional theories focus on textual meaning or historical context, this article proposes that constitutional interpretation must also be approached ontologically—understanding the very essence of interpretation. Drawing on Gadamer’s philosophical hermeneutics, this study suggests that constitutional interpretation should be viewed as a dynamic process influenced by historical understanding, language, and societal context. Constitutional hermeneutics, as a theoretical framework, opposes rigid methodologies and emphasizes the role of language, historical context, and prejudices in shaping meaning. It offers a more holistic understanding, allowing for the Constitution to evolve with societal changes, ensuring its relevance in modern governance. This approach provides a more comprehensive solution to the challenges posed by the debate between originalism and non-originalism.